Detecção molecular e sorológica da infecção por Mycobacterium Leprae em casos e comunicantes de hanseníase e escolares de Oriximiná (PA) - FERREIRA, Denis Vieira Gomes (Universidade Federal do Pará, 2017)
Leprosy is a chronic infectious disease that primarily affects skin and peripheral nerves and its clinical signs are lesions with abnormal pigmentation and sensitivity. Its etiologic agent is Mycobacterium leprae, an obligate intracellular bacillus, acid fast rod-shaped straight or slightly curved. The transmission occurs through the upper airway, and the default host immune ranges from a high cell-mediated immune response, known as Th1 response, a high susceptibility to infection with high humoral immune response, Th2 response. This study aimed to examine clinical and socio-epidemiological information to correlate with levels of IgM anti-PGL-1 in plasma, and molecular detection of M. leprae in nasal swabs from cases and contacts of leprosy between 2004 and 2008, and schoolchildren from public schools in the city of Oriximiná Para. The results show that: 1) leprosy patients have poor housing and food, with almost 50% of food deprivation, 2) approximately 45% of clinically healthy presents IgM anti-PGL-1 positive, regardless of age, period of living with index cases or the presence or absence of a BCG scar and 3) the DNA of M. leprae is found in 15- 30% of cases and contacts, and only 1.6% of students did not show correlation with ELISA IgM anti-PGL-1, with the clinical form of the disease or the duration of the leprosy patients treated with MDT in the 5 years before data collection. Thus, the positivity of ELISA IgM anti-PGL-1 seems to indicate the magnitude of the exposure of a population to M. leprae, which may contribute to epidemiological studies and the definition of priority population groups to conduct active case finding of leprosy in a given community.